2017
DOI: 10.1007/s12039-017-1245-y
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown of universal Lindemann criterion in the melting of Lennard-Jones polydisperse solids

Abstract: It is commonly believed that melting occurs when mean square displacement (MSD) of a particle of crystalline solid exceeds a threshold value. This is known as the Lindemann criterion, first introduced in the year of 1910 by Lindemann. However, Chakravarty et al. demonstrated that this common wisdom is inadequate because the MSD at melting can be temperature dependent when pressure is also allowed to vary along the coexistence line of the phase diagram [Chakravarty C, Debenedetti P G and Stillinger F H 2007 J. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…In general, a critical Linderman index value, 0.1, is regarded as the melting indicator. 61 By viewing the radial distributions of the atomic Lindeman index (Fig. 10f and g), the particle surface atoms exhibit a higher Lindemann index, reaching 0.15 at 1800 K. The surface atoms have smaller coordination numbers and greater energies than the atoms in the interior regions of the particle.…”
Section: Resultsmentioning
confidence: 98%
“…In general, a critical Linderman index value, 0.1, is regarded as the melting indicator. 61 By viewing the radial distributions of the atomic Lindeman index (Fig. 10f and g), the particle surface atoms exhibit a higher Lindemann index, reaching 0.15 at 1800 K. The surface atoms have smaller coordination numbers and greater energies than the atoms in the interior regions of the particle.…”
Section: Resultsmentioning
confidence: 98%
“…This critical value saturates to a value of about 0.11 for all temperatures, in good agreement with the experimental value of 0.12. Further, it was shown that the Lindemann rule breaks down for polydisperse systems, 183 as the increased root-meansquare amplitude of the smaller particles plays a role in the segregation of them prior to melting, although melting itself remain discontinuous.…”
Section: General Aspectsmentioning
confidence: 99%
“…Consequently, simple melting "rules" formulated from experimental observation have been popular. The Lindemann melting criterion [13][14][15] is perhaps the most widely used melting rule, and it states that melting occurs when the root mean amplitude of vibration exceeds a threshold value in relation to the nearest neighbor distance (originally stated to be 10%). At melt, all atoms vibrate at the Einstein frequency so the equipartition theorem can be used to equate the amplitude of vibration to the temperature, yielding š‘‡ ( =…”
Section: Material-level Microscopic Descriptionmentioning
confidence: 99%